A cross‐sectional study of thyroid function in 66 patients with bipolar disorder receiving lithium for 10–44 years. (31st October 2014) - Kraszewska, Agnieszka; Chlopocka‐Wozniak, Maria; Abramowicz, Maria; Sowinski, Jerzy; Rybakowski, Janusz K
<x xml:space="preserve">Abstract</x> Objectives An important side effect of lithium therapy is an influence on thyroid function. It is unclear whether there is a significant association between thyroid function and duration of lithium administration. The aim of the present cross‐sectional study was to measure levels of thyroid hormones and antibodies in patients with bipolar disorder receiving lithium for more than ten years. Methods The study was performed in 66 patients (21 males, 45 females) with bipolar mood disorder, receiving lithium for 10–44 (21 ± 9; mean ± standard deviation) years. Thyroid‐stimulating hormone (TSH), free thyroxine (fT3), and free triiodothyronine (fT4) were measured by the microparticle enzyme immunoassay. Thyroid peroxidase (TPO) antibodies, thyroglobulin (TG) antibodies, and TSH receptor (TSH‐R) antibodies were measured by the radioimmunoassay. Results Some features of hypothyroidism were found in ten (22%) female patients (seven received levothyroxine and three had increased TSH). No abnormality in thyroid hormones was found in male patients. A significant percentage of patients had abnormally high levels of anti‐TPO, and anti‐TG antibodies, which correlated with TSH and fT3 concentrations. There were no differences in thyroid function between patients receiving lithium for 10–20 years and those taking the drug for more than 20 years. Conclusions These results confirm the greater susceptibility of female subjects for disturbances of thyroid hormones during lithium therapy, with one‐fifth of them showing some features of hypothyroidism. Abnormally high levels of anti‐TPO and anti‐TG antibodies were shown in a significant proportion of patients. However, in contrast to the effect of lithium on kidney function, our results do not show an association between the duration of lithium therapy and thyroid dysfunction.